Quantum physics and consciousness: a (strong) defense of panpsychism (2018)
Probably the crux of quantum science is the relationship between consciousness and reality. The name for that relation is varied, and points out to a most fundamental problem, namely the possibility to overcome dualism. In science and philosophy at large, determinism and reductionism have already been tackled, if not superseded. The trouble though remains with dualism. This paper argues in favor of a radical relationship between reality and consciousness based on quantum theory. Such a relation is panpsychism, which can be translated and grasped in various other forms. The arguments are provided and some conclusions are drawn.